The correlation of stoichiometry between boron-rich LaB6 targets and LaB6 films. Issue 1 (January 2015) - Wu, Yan; Min, Guanghui; Chen, Defang; Zhang, Lin; Yu, Huashun
Abstract: Nanostructured B-doped LaB6 films prepared by DC magnetron sputtering method were expected to obtain stoichiometric LaB6 film for stable optical performance. The proportion of each element at the interface was deduced from X-ray photoelectron spectroscopy (XPS) data using the B/La atomic ratio and decomposition of lanthanum peak. A linear relation was observed between adding amount of boron and the B/La atomic ratio of the film surface layers. The composition of prepared LaB6 thin films reached LaB5.949±0.2, nearly at the stoichiometric ratio. It was concluded that practical curve fitting procedures for various lanthanum chemical states in thin film surfaces were demonstrated and results obtained by the curve-fitting procedure were reliable. A series of techniques such as X-ray diffraction (XRD), atomic force microscope (AFM) and scanning electron microscopy (SEM) were employed to characterize the structure, surface morphology and particle size of B-doped and undoped LaB6 thin films. Combining the information from XRD and topographic images, fracture cross-sections, effects of boron on grain refinement had been discussed and confirmed by the decrease of surface roughness, height distribution, average particle size and thickness of thin films.